Insights into perovskite-catalyzed peroxymonosulfate activation: Maneuverable cobalt sites for promoted evolution of sulfate radicals - Duan, Xiaoguang; Su, C.; Miao, J.; Zhong, Y.; Shao, Zongping; Wang, Shaobin; Sun, H. (Elsevier BV, 2018)
© 2017 Elsevier B.V. Metal-based catalysis has significantly contributed to the chemical community especially in environmental science. However, the knowledge of cobalt-based perovskite for aqueous phase oxidation still remains equivocal and insufficient. In this study, we discovered that Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-d (BSCF) perovskite was exclusively effective for peroxymonosulfate (PMS) activation to produce free radicals, whereas the BSCF was inert to activate peroxydisulfate (PDS) and hydrogen peroxide. The BSCF/PMS exhibited superior performance to the benchmark Co 3 O 4 nanocrystals and other classical PMS activators such as a-MnO 2 and spinel CoFe 2 O 4 , meanwhile achieving an impressive stability with manipulated cobalt leaching in neutral and basic environment. In situ electron paramagnetic resonance (EPR) revealed the evolution of massive sulfate radicals (SO 4 [rad] - ) and hydroxyl radicals ([rad]OH) during the oxidation. A comprehensively comparative study of BSCF and Co 3 O 4 nanocrystals was performed, including electrochemical impedance spectroscopy (EIS) and cyclic voltammograms (CV) in PMS solution as well as hydrogen temperature-programmed reduction (H 2 -TPR) and oxygen temperature-programmed desorption (O 2 -TPD) tests. The results unveil that the cobalt-based perovskite, BSCF, exhibited a better electrical conductivity and redox potential than the spinel cobalt oxide to interact with PMS. More importantly, the oxygen vacancies and less-electronegativity A-site metals may secure cobalt sites with a lower valence state for donating electrons to PMS simultaneously for radical generation. This study advances the mechanism of cobalt-based heterogeneous catalysis in environmental remediation.